Effects of COVID-19 on Multilingual Communication - Pilgun, Maria; Raskhodchikov, Aleksei N.; Koreneva Antonova, Olga (Frontiers in Psychology, 2022)
The paper presents the results of a study on the analysis of the perception of COVID-19 by Spanish-, German- and Russian-speaking social media actors after the emergence of vaccines and attitudes towards vaccination. The empirical base of the study was corpus data, materials from online media, social networks, microblogging, blogs, instant messengers, forums, reviews and video hosting data. The Spanish-language database included 6,640,912 tokens and 43,251,900 characters; the German-language database included 16,322,042 tokens and 109,139,405 characters; and the Russian-language database included 16,310,307 tokens and 109,060,935 characters. With a neural network approach, a multilingual analysis was performed, which made it possible to analyze the topic structure and the semantic network with the allocation of the semantic core and the associative network. Differential and integral features of the identified structures based on the material of these three databases made it possible to determine the general and different characteristics of the perception by Spanish-, German- and Russian-speaking users of the development of the pandemic, a number of social problems, attitudes towards various types of vaccines, observance of preventive measures and readiness for vaccination.